Properties of BaBi2Ta2O9 thin films prepared by chemical solution deposition technique for dynamic random-access memory applications - Foschini, C. R.; Joshi, P. C.; Varela, José Arana [UNESP]; Desu, S. B. (Springer Nature, 1999)
We report on the properties of BaBi2Ta2O9 (BBT) thin films for dynamic random-access memory (DRAM) and integrated capacitor applications. Crystalline BBT thin films were successfully fabricated by the chemical solution deposition technique on Pt-coated Si substrates at a low annealing temperature of 650°C. The films were characterized in terms of structural, dielectric, and insulating properties. The electrical measurements were conducted on Pt/BBT/Pt capacitors. The typical measured small signal dielectric constant and dissipation factor, at 100 kHz, were 282 and 0.023, respectively, for films annealed at 700°C for 60 min. The leakage current density of the films was lower than 10-9 A/cm2 at an applied electric field of 300 kV/cm. A large storage density of 38.4 fC/μm2 was obtained at an applied electric field of 200 kV/cm. The high dielectric constant, low dielectric loss and low leakage current density suggest the suitability of BBT thin films as dielectric layer for DRAM and integrated capacitor applications.
Keywords: Annealing; Barium compounds; Capacitors; Crystal structure; Crystallization; Deposition; Dynamic random access storage; Insulating materials; Leakage currents; Permittivity; Phase transitions; Thin films; Chemical solution deposition; Orthorhombic phase; Dielectric films